FDZ data description: Regional real estate price indices for Germany (RWI-GEO-REDX) - Version 13: 2008-11/2023 - Patrick Thiel (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
The FDZ Ruhr at RWI offers price indices for apartments and houses (rentals and sales) in Germany, commencing in 2008. The price indices are derived from the RWI-GEO-RED real estate dataset, which integrates real estate listings from ImmoScout24. Three types of hedonic regressions are performed to allow for comparisons across time (annual or quarterly), across regions (1 x 1 km, municipality, and district), and in combination across time and regions. Furthermore, starting with V13, we also offer a combined index, whereby all three data sources (apartment rents and sales, and house sales) are combined into a single index. The data are publicly available (PUF) and can be requested from the FDZ Ruhr website. A weakly anonymized version (SUF) is also available for researchers upon request. This data report constitutes an updated version of previous reports and refers to RWI-GEOREDX v13, which encompasses data up to November 2023. – – Das FDZ Ruhr am RWI stellt Preisindizes für Wohnungen und Häuser (Vermietung und Verkauf) in Deutschland ab dem Jahr 2008 zur Verfügung. Die Preisindizes basieren auf dem Immobiliendatensatz RWI-GEO-RED, der Immobilienangebote von ImmoScout24 zusammenfasst. Wir führen drei Arten von hedonischen Regressionen durch, um Vergleiche über die Zeit (jährlich oder vierteljährlich), über Regionen (1 x 1 km, Landkreise oder Gemeinden) und in Kombination über Zeit und Regionen zu ermöglichen. Seit Version 13 bieten wir außerdem einen kombinierten Index, der aus den drei Einzeldatensätze (Wohnungsmiete, Wohnungskauf und Hauskauf) besteht, an. Die Daten sind öffentlich zugänglich und können auf der Website des FDZ Ruhr angefordert werden. Eine schwach anonymisierte Version ist für Forscher auf Anfrage ebenfalls erhältlich. Die vorliegende Datensatzbeschreibung ist eine aktualisierte Version früherer Berichte und bezieht sich auf RWI-GEO-REDX v13, die Daten bis November 2023 umfasst.
Keywords: 330; Immobilienpreis; Miete; Preisindex; Deutschland